Production of freeze-dried human antihaemophilic cryoprecipitate. Issue 10 (October 1981) - Millgan, G; Graham, R; Hanratty, S; Muir, W; Mitchell, R
Abstract : Concentration of factor VIII from fresh plasma by cryoprecipitation remains the basis for preparation of products used to treat haemophilia A. This paper describes the preparation of a factor VIII concentrate from small plasma pools in transfusion centres with drying facilities. The dried concentrate from one litre of plasma dissolves very well in 50 or 100 ml of distilled water and contains around 500 IU per bottle. The specific activity per mg protein is 0.19 IU and the fibrinogen concentration is half that in frozen cryoprecipitate. This method of drying causes no appreciable loss in the factor VIIIC activity and little denaturation as shown by the factor-VIII-related antigen/factor VIIIC ratio of 1.7.